1986
DOI: 10.1136/bmj.293.6556.1195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of near normoglycaemia for two years on progression of early diabetic retinopathy, nephropathy, and neuropathy: the Oslo study.

Abstract: Forty five insulin dependent diabetics were randomised to treatment with continuous subcutaneous insulin infusion (CSII), multiple insulin injections (five or six daily), or conventional twice daily insulin injections. Near normoglycaemia was obtained with CSII and multiple injections but not with conventional treatment (p Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
136
4
7

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(154 citation statements)
references
References 33 publications
7
136
4
7
Order By: Relevance
“…HbA1c results reflect average plasma glucose concentration during the preceding 2–3 months [17]. The firm association between HbA1c results and late complications of DM was first documented in a Norwegian study [18]. Due to its high pre-analytical stability, high reproducibility, less day-to-day perturbations during periods of stress and illness, and convenience (no need for prior fasting or glucose overload), HbA1c is being increasingly utilised in medical settings for both diagnosis and follow-up of patients with DM [5].…”
Section: Discussionmentioning
confidence: 99%
“…HbA1c results reflect average plasma glucose concentration during the preceding 2–3 months [17]. The firm association between HbA1c results and late complications of DM was first documented in a Norwegian study [18]. Due to its high pre-analytical stability, high reproducibility, less day-to-day perturbations during periods of stress and illness, and convenience (no need for prior fasting or glucose overload), HbA1c is being increasingly utilised in medical settings for both diagnosis and follow-up of patients with DM [5].…”
Section: Discussionmentioning
confidence: 99%
“…The study periods lasted from a minimum of 5 weeks to a maximum of 2 years. Upon our request, the authors of the Oslo Study [17,18,23,[25][26][27][28][29] told us that the study was originally intended to last for 2 years, but was later extended to 4 years. Due to incomplete data records after 4 years, only the results from the 2 year analysis were considered for this review.…”
Section: Description Of Included Trialsmentioning
confidence: 99%
“…Long-term monitoring of glycaemic control by HbA 1 c was introduced [1] as well as patient education, self-monitoring of blood glucose [2], insulin treatment with basal-bolus concept, insulin pens and continuous subcutaneous insulin infusion with insulin pumps [3]. In several randomised clinical trials improved glycaemic control has been found to reduce the development of retinopathy and nephropathy [4,5,6,7]. There has, however, been a debate about whether it is possible to achieve the same results in an unselected population.…”
mentioning
confidence: 99%